INFORMATION PROCESSING DEVICE, INFORMATION PROCESSING METHOD, AND PROGRAM - SASAKI, Toshiyuki; SAKURAI, Yuta; KAMIO, Kazunori; KAWATA, Satoshi (2022)
This information processing device (30) comprises a signal acquisition unit (31), a passive depth estimation unit (34), and a fusion unit (35). The signal acquisition unit (31) extracts, from light reception data, active information indicating the time of flight of reference light (PL) and passive information (PI) indicating two-dimensional image information for a subject (SU) obtained using ambient light (EL). The passive depth estimation unit (34) generates passive depth information (PDI) on the basis of the passive information (PI). The fusion unit (35) generates depth information (DI) for the subject (SU) by fusing active depth information (ADI) generated on the basis of the active information with the passive depth information (PDI). La présente invention concerne un dispositif (30) de traitement d'informations comportant une unité (31) d'acquisition de signaux, une unité (34) d'estimation passive de profondeur, et une unité (35) de fusion. L'unité (31) d'acquisition de signaux extrait, à partir de données de réception de lumière, des informations actives indiquant le temps de vol d'une lumière de référence (PL) et des informations passives (PI) indiquant des informations d'image bidimensionnelle concernant un sujet (SU) obtenues en utilisant la lumière ambiante (EL). L'unité (34) d'estimation passive de profondeur génère des informations passives de profondeur (PDI) d'après les informations passives (PI). L'unité (35) de fusion génère des informations de profondeur (DI) concernant le sujet (SU) en fusionnant des informations actives de profondeur (ADI) générées d'après les informations actives avec les informations passives de profondeur (PDI). 情報処理装置（３０）は、信号取得部（３１）とパッシブデプス推定部（３４）とフュージョン部（３５）とを有する。信号取得部（３１）は、受光データから、参照光（ＰＬ）の飛行時間を示すアクティブ情報と、環境光（ＥＬ）による被写体（ＳＵ）の２次元画像情報を示すパッシブ情報（ＰＩ）と、を抽出する。パッシブデプス推定部（３４）は、パッシブ情報（ＰＩ）に基づいてパッシブデプス情報（ＰＤＩ）を生成する。フュージョン部（３５）は、アクティブ情報に基づいて生成されたアクティブデプス情報（ＡＤＩ）にパッシブデプス情報（ＰＤＩ）をフュージョンして被写体（ＳＵ）のデプス情報（ＤＩ）を生成する。